(untitled) (Journal of Contemporary Philology, 2024)
This paper analyses the expression of the monstrous-feminine in Mesopotamian, Ancient Greek and Albanian myths and folklore, while connecting them with and interpreting them through ideas expressed by Barbara Creed (1993) in her book The Monstrous-Feminine: Film, Feminism, Psychoanalysis. In this paper we can notice matters of the monstrous-feminine that connect between different cultures and geographies, what these matters show us about the cultural perception towards femininity, and how these matters have often been used to portray the danger and risk perceived by a male-dominated society, and the connection these myths and mythological creatures have with Creed’s interpretation of the monstrous-feminine in horror films. By studying this topic, we will better understand how the mentioned cultures, but not only, have portrayed female monsters and monstrous beings, what role they have had in the culture-building of these societies, how they reflect general psycho-social tendencies, and how they continue to be influential to this day in our understanding of gender-roles, societal duties and metaphysical views.